Anti-arthritic, immunomodulatory, and inflammatory regulation by the benzimidazole derivative BMZ-AD: Insights from an FCA-induced rat model - Ahmad Haseeb; Anjum Irfan; Usman Halima; Mobashar Aisha; Shabbir Arham; Bin Jardan Yousef A.; Metouekel Amira; Dauelbait Musaab; Bourhia Mohammed (Open Life Sciences, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease causing joint inflammation, deformity, cartilage deterioration, and pain. Benzimidazole derivatives exhibit various pharmacological properties. This study evaluated the antiarthritic, immunomodulatory, and anti-inflammatory potential of a benzimidazole derivative 2-(2-(benzylthio)-1H-benzo[d]imidazol-1-yl)-N′-(4-nitrobenzylidiene) acetohydrazide (BMZ-AD) in a Freund’s complete adjuvant (FCA)-induced arthritic rat model. FCA was administered on day 0, and treatment with BMZ-AD (25 mg/kg, 50 mg/kg, and 75 mg/kg) and piroxicam (10 mg/kg) began on day 7 and continued up to 28 days. Rats were sacrificed on day 28. Arthritis was assessed using an arthritic scoring index, and paw edema was measured with a digital water plethysmometer. Biochemical and hematological parameters were analyzed, reverse transcription polymerase chain reaction measured the mRNA expression of tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), and molecular docking evaluated BMZ-AD interactions with these proteins. Enzyme-linked immunosorbent assay determined prostaglandin E2 levels. BMZ-AD treatment reduced inflammation, pannus formation, and pro-inflammatory cytokines (TNF-α and IL-6) and decreased PGE2 levels, comparable to piroxicam. Blood profiles improved with significant reductions in white blood cells and platelets in treatment groups. BMZ-AD demonstrated antiarthritic, anti-inflammatory, and immunomodulatory properties, suggesting that it could be a potential drug for RA treatment with fewer side effects.